Pengaruh Terpaan Iklan Susu Formula di TV, Kelompok Acuan, Tingkat Sosial Ekonomi, dan Pengetahuan Ibu Terhadap Perilaku Ibu Untuk Memberikan ASI Ekslusif di Kabupaten Semarang - Dini Hidayanti (Program Studi Ilmu Komunikasi Universitas Paramadina, 2015)
Marketing and promotion of breastfeeding (ASI) which are not profitable materially must compete with the marketing of formula milk products that gain millions of dollars for multinational companies. The conditions in the field indicate that the success of the Scope of Exclusive Breastfeeding in Semarang District, compared to the Minimum Service Standards (SPM) in 2013 which targeted the infants exclusively breastfed of 80%, is still far enough at 36.29%. This means that the coverage of infants receiving exclusive breastfeeding in Semarang District is still far below expectations. The aims of the research were to determine the effects of Exposure of Formula Milk Advertisements on TV, Reference Group, Socioeconomic Level and Mother’s Knowledge on Mother’s Behavior to Provide Exclusive Breastfeeding in Semarang District The theory used was the Elaboration Likelihood Model (ELM) which explains that the decision made depends on the path taken in processing a message. Social Cognitive Theory explains that mother’s behavior to give exclusive breastfeeding (behavioral determinants) can be influenced by environmental determinants (the exposure of formula milk advertisements on TV, reference group, socioeconomic level) and personal determinants (mother's knowledge). This research was explanatory by observing the effects among the variables of research and testing the hypotheses that had been formulated. The population in this research was the mothers of the infants aged 7-12 months living in Semarang District. The research samples were spread over 5 (five) different locations in 5 (five) villages in Semarang District so that the sampling technique used was multi-stage random sampling. The data collection instrument was the questionnaires read to the respondents through the method of interview. The research results to 97 respondents indicate that there are 3 (three) independent variables that affect mother's behavior in breastfeeding exclusively. The three independent variables are the Exposure of Formula Milk Advertisement on TV (X1) having negative effect of -0196 or 19.6 percent, Respondents’ Socioeconomic Level (X3) of 0.227, or 22.7 percent, and Mother’s Knowledge (X4) having positive effect of 0.496 or 49.6 percent. In other hand, the variable of reference group (X2) does not significantly affect the variable of mother's behavior in exclusive breastfeeding. The contribution of the four independent variables on the dependent variables is 53 percent, so 47 percent of the determinant factors out of the examined variables that influence mother’s behavior in breastfeeding exclusively are still left. Keywords: Advertisement Exposure, SES, Mother’s Knowledge, Exclusive Breastfeeding